Effect Evaluation and Influencing Factors of E-Learning Training in Colleges - Li Zhou (Kassel University Press, 2021)
E-learning is a teaching model formed during the informatization of colleges. It is of great significance to the promotion of teaching reform. This paper tries to evaluate the training effect of e-learning among college students, understand their perception and expectation of e-learning, and demonstrate the importance of the training to the practical ability and professional knowledge utilization of college students. In addition, the factors affecting e-learning training in colleges are evaluated one by one. The results show that e-learning training effect can be assessed well with an evaluation index system (EIS), consisting of a response layer, a learning layer, a behavior layer, and a result layer. The training effect of e-learning is influenced by the trainee characteristics, working environment, and training design. The research lays a theoretical basis for applying e-learning training in teaching.